Post-pandemic pedagogical lag of quilombola students in the Monte Alegre-ES Community (Research, Society and Development, 2022)
The COVID-19 pandemic has significantly interfered with the educational structure worldwide. Several educational institutions needed to change pedagogical practices in order to meet social distancing standards. In this sense, information and communication technologies were presented as a tool capable of guaranteeing that the teaching and learning process could happen through remote teaching, however, the lack of adequate tools to access networks or limited access to it became a problem. for basic education students. The problem gains greater proportions in quilombola communities, such as the one that occurred in the Municipal School of Basic Education (EMEB) Monte Alegre, located in the district of Pacotuba, belonging to the Municipality of Cachoeiro de Itapemirim - ES. Even with the availability of printed materials to students, teachers were concerned about the increase in the rate of school lag among their students. In this way, this article aims to alert about the possible impacts caused by the insertion of remote teaching during the COVID-19 pandemic in schoolchildren belonging to early childhood education in the quilombola community of Monte Alegre, in the Municipality of Cachoeiro de Itapemirim - ES.